Association Between Components of Metabolic Syndrome and Cognitive Impairment among Middle-Aged and Elderly in Indonesia: A Nationwide Survey - Sandy Ardiansyah; Bayu Satria Wiratama; Shyh-Hsiang Lin (Journal of Global Nutrition, 2021)
Cognitive impairment is common among population worldwide which become an increasingly important health issue related with aging. Indonesia is one of low-middle income countries with reach the era of aging, as the population aged 60 years and over is 10.0% in 2020.The purpose of this study was to investigate associations between components of metabolic syndrome (MetS) and cognitive impairment among middle-aged and elderly Indonesians. Cognitively impaired was measured with the questionnaire derived from the instrument of telephone interview for cognitive status (TICS). Analysis of covariance was used to examine the differences and multivariate with logistic regression analysis of the odds of cognitive impairment. Setting on this study was using The Indonesia Family Life Survey (IFLS)-5 conducted in 2014-2015 with 1532 participants were placed into middle-aged and elderly. This study found that central obesity and dyslipidemia were less likely to have cognitive impairment among middle-aged and elderly. (OR adjusted for age and sex 0.67; 95% CI 0.37~1.20; p=0.175). In conclucion, central obesity and dyslipidemia were less likely to have cognitive impairment among middle-aged and elderly in Indonesia. Our findings suggest that middle-aged people should manage their waist circumference in order to prevent cognitive impairment as they age.